IMPLEMENTASI KOMUNIKASI ORGANISASI IGTK-DEPOK DALAM UPAYA MENINGKATKAN KUALITAS PELAYANAN DAN KOMPETENSI ADMINISTRASI, GURU DAN KEPALA SEKOLAH - Mariam, Iis; Wartiningsih, Endah; Purwinarti, Titik; Putro, Zaenal Abidin Eko (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Politeknik Negeri Bandung, 2023)
The collaboration of professional organizations is now important in assisting the development of school organizations including the staff and school leaders so that the organization grows and is empowered. Currently, organizational change is becoming dynamic, requiring members and organizational leaders to be more creative and innovative so that the organization grows into a learning organization. Kindergarten education is one form of early childhood education (PAUD) which has an important role in developing a child's personality and as a foundation in entering the next level of education. In an effort to improve the quality of Kindergarten educational organizations, one part of the Pentahelix concept, namely the involvement of associations, plays an important role. The problems in this study are: (a) what is the role of the Depok-West Java Kindergarten Teacher Association (IGTK) in improving the competence of administrative staff, teachers and principals as a form of implementing the pentahelix concept?, (b) How is organizational communication from IGTK Depok in improving the quality of administrative services for administrative staff, teachers and school principals to students, parents and the community. This research is a follow-up to community service activities that have been carried out for teachers and kindergarten principals in Sawangan sub-district, Depok who are members of IGTK-Depok. The analytical method used in this community service training activity is descriptive qualitative. Data collection techniques were carried out through observation, interviews with school principals, head of IGTK Depok, and questionnaires distributed via google form to 23 people (teachers and kindergarten principals). The results of the training show that the role and function of IGTK is important. Answered strongly agree (73%) and IGTK has played a role in increasing the competence of administrative staff, teachers and principals answered strongly agree (67%), IGTK has had an impact on improving the service quality of kindergarten school organizations in students, parents and the community have answered strongly agree (70%), administrative staff, teachers and school principals are able to handle complaints from students/parents/community answered agree (73%). The Pentahelix concept also has an impact on the collaboration that is built not only between administrative staff, teachers and school principals but also with the government, the community (parents of students), and the media. with formal language followed by maintained voice intonation answered agree (60%), administrative staff, teachers and principals are friendly and polite in providing services to parents/community students answered agree (60%), administrative staff, teachers and principals providing solutions to students/parents regarding problems in the learning process answered strongly agree (53%), the services provided by administrative staff, teachers and principals have a positive impact on the school/organization (strongly agree (67%).